Analysis of Wind Energy Potential On Nusa Penida Island Using The Weibull Distribution: Evaluation of Power Density and Intermittency - Herlambang, Amanda Austin; Dewi Wirastuti, Ni Made Ary Esta; Manuaba, Ida Bagus Gede (ELKHA : Jurnal Teknik Elektro, 2025)
Nusa Penida Island faces increasing energy demands driven by tourism and development, highlighting the need for sustainable energy solutions. While previous wind studies in Indonesia have primarily focused on larger islands, this research evaluates Nusa Penida"™s wind energy potential using the Weibull distribution method for power density and intermittency analysis. Unlike prior studies, this research incorporates seasonal variations and probabilistic modeling to provide a more accurate assessment of wind intermittency. Statistical analysis of 2019"“2020 wind speed data from NASA Power reveals stable wind conditions, with an average power density of 104 W/m ², making it suitable for medium scale wind energy projects. Peak wind speeds occur mid year, optimizing conditions for energy harvesting, while intermittency analysis indicates that wind speeds fall below 3 m/s approximately 30% of the time, emphasizing the need for energy storage or hybrid systems. This research quantifies the impact of intermittency on energy planning, offering a data driven approach to support Indonesia"™s renewable energy diversification and reduce reliance on fossil fuels. The findings establish Nusa Penida"™s feasibility for wind energy deployment, contributing to enhanced energy resilience in remote island communities.